1999
DOI: 10.1038/sj.gt.3301003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prior exposure to herpes simplex virus 1 on viral vector-mediated tumor therapy in immunocompetent mice

Abstract: Replication-competent, attenuated mutants of herpes simrespectively. Established tumors were subsequently plex virus type 1 (HSV-1) have been shown to be effitreated intratumorally with a multi-mutated HSV-1, G207. cacious for tumor therapy. However, these studies did not G207 inhibited tumor growth to a similar extent whether address the consequences of prior exposure to HSV, as the mice were seropositive or not. We next examined the will be the case with many patients likely to receive this effect of multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(57 citation statements)
references
References 49 publications
3
53
1
Order By: Relevance
“…This demonstrated that tumours were effectively treated even following prior immunization with HSV, there being no detectable difference in the magnitude of the anti-tumour effect as compared to the previous experiments reported above ( Figure 9). Thus, as previously reported for a previous version of oncolytic HSV, 38 prior immunity to HSV does not have a significant effect on the ability of the virus to treat tumours.…”
Section: Pre-existing Anti-hsv Immunity Does Not Affect the Anti-tumosupporting
confidence: 80%
See 1 more Smart Citation
“…This demonstrated that tumours were effectively treated even following prior immunization with HSV, there being no detectable difference in the magnitude of the anti-tumour effect as compared to the previous experiments reported above ( Figure 9). Thus, as previously reported for a previous version of oncolytic HSV, 38 prior immunity to HSV does not have a significant effect on the ability of the virus to treat tumours.…”
Section: Pre-existing Anti-hsv Immunity Does Not Affect the Anti-tumosupporting
confidence: 80%
“…38 Balb/c mice were immunized i.p. with 5 Â 10 3 pfu wild-type HSV1 (17+) in PBS 5 weeks before tumour induction.…”
Section: Prior Immunization Of Micementioning
confidence: 99%
“…Neither antibody nor cellular proliferative responses elicited in mice immunized with a replication-defective HSV vector were affected by prior exposure to HSV [38]. Additionally, treatment of tumor-bearing mice with oncolytic HSV was not adversely effected even in mice with prior HSV-1 immunity [36]. Other studies in mice seropositive for HSV-1 have indicated that humoral and cell-mediated immune responses are significantly reduced following immunization with replication-defective HSV vectors as compared to immunization of HSV-1 naïve mice [69].…”
Section: Discussionmentioning
confidence: 92%
“…Herpes simplex virus type-1 (HSV-1) with deletions in the Δγ 1 34.5 gene is replication-competent but is aneurovirulent [23]. Attenuated HSV-1 recombinants are attractive as HIV-1 vaccine vectors for multiple reasons: i) herpesvirus vectors can infect dendritic cells and stimulate potent, longlasting CMI responses [24][25][26][27][28]; ii) attenuated HSV can establish latency and reactivate with the potential to prolong an immune response [29,30]; iii) several nonessential genes can be deleted and replaced with multiple foreign gene inserts (up to 30 kb) [31]; vi) HSV Δγ 1 34.5 viruses have been safe during human use in clinical trials, including intracranial injection at high doses [32][33][34][35]; and v) although prior immunity to HSV has a variable effect on vector efficacy in gene therapy applications, it does not impair either antibody or CMI responses elicited against immunogens expressed from HSV vectors [36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…49 We have recently used N18 murine neuroblastoma cells that are moderately susceptible to G207 and reproducibly form s.c. or intracerebral tumors in syngeneic A/J mice. 50,51 This immunocompetent mouse tumor model has proven suitable for testing of the therapeutic efficacy of recombinant HSV-1. In this study, we evaluate the effect of GCV on G207 tumor therapy in vitro using several different cell lines and in vivo using the N18 mouse tumor model.…”
mentioning
confidence: 99%